Pożary odpadów a narażenie strażaków na substancje toksyczne - Susło, Robert; Paplicki, Mateusz; Dopierała, Karol; Wrzesiński, Janusz; Drobnik, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In Poland in recent years more and more waste have been set on fire, thus intervening firefighters are at increased risk of suffering intoxication from fumes. Based on current literature and legal regulations review, characteristics of relevant toxic substances, associated health hazards and preventive measures were analyzed. In order to prevent negative health effects it is crucial not only to equip firefighters with adequate personal protective equipment and clothing but also to introduce obligatory monitoring their proper usage based on biologic markers of intoxicatio
Keywords: strażak; pożar odpadów; toksyczność oparów; zagrożenie dla zdrowia